Uso das terapias laser e LED (Light-Emitting Diode) de baixa intensidade para aumentar o desempenho muscular: do in vitro e experimental ao uso clínico - Ferraresi, Cleber (2014)
Recent studies have used low-level laser therapy (LLLT) and LEDs (light-emitting diodes - LEDT) to increase muscle performance in experimental models and randomized clinical trials. However, the effects of these therapies on muscle tissue are not well understood, especially related to their mechanisms of action and clinical use. The objective of this thesis was to investigate the effects of LLLT and LEDT on muscle tissue through in vitro, experimental models and clinical trials to elucidate the main mechanisms of action of these therapies on muscle tissue submitted to fatigue tests and/ or strength training programs to guide the clinical practice. Among the mechanisms of action, we highlight a modulation of mitochondrial metabolism, synthesis of ATP (adenosine triphosphate) and glycogen, muscle cell proliferation, antioxidant defenses and a gene expression modulation quantified by real time polymerase chain reaction (RT-PCR) and microarrays (whole human genome). To accomplish these objectives, we conducted an in vitro study with muscle cell line culture, two experimental studies with animals submitted to fatigue tests and physical training, and five clinical studies that investigated the effects of LLLT and LEDT on muscular pre-conditioning (LLLT/ LEDT application before exercise) and post-exercise muscle recovery (LLLT/ LEDT application after exercise) in athletes, non-athletes and young men genetically comparable (identical twins) submitted to official games of volleyball, sub maximal and maximal tests of effort, and physical training programs, respectively. In vitro, experimental and clinical studies, added to an extensive literature review included in this thesis, allowed us to understand that there is a time-response to muscle cells absorb the energy of lasers/ LEDs and transform that energy into biochemical responses to increase muscle performance in muscular pre-conditioning regimen, or accelerate postexercise muscle recovery. In addition, LLLT/ LEDT applied over the muscle tissue shows also a pattern of dose-response which appears to be dependent of the objective, i.e., prevention of muscle damage or stimulation of energy metabolism, ATP synthesis, gene expression and improved muscle performance.